TYPES OF COLLABORATIVE CONTINUOUS PROFESSIONAL DEVELOPMENT IN PHYSICAL EDUCATION: A DIALOGUE - da Costa Filho, Roraima Alves [UNESP]; Beni, Stephanie; Aubin, Anne-Sophie; Iaochite, Roberto Tadeu [UNESP]; Fletcher, Tim; Borges, Cecilia (My University, 2022)
This paper presents a dialogue between researchers from three collaborative continuous teacher professional development (CCPD) projects, each of which involved a different theoretical framework and research design. Discussing our unique contexts and the CCPD approaches we used enabled us to engage in an appreciative inquiry, in which we sought to acknowledge and build upon the strengths of each project and consider possibilities for the future. Findings highlight complexities of CCPD at different levels from the small-scale to the large, requiring thoughtful planning and implementation. Promoting intimacy, organizing schedules and timetables, and combining different modes of support are challenges that require contextualized responses. There is a need for CCPD facilitators and researchers to consider not only characteristics of effectiveness when choosing a CCPD approach, but also alignment with their own personal beliefs and theories of learning, as well as the beliefs, interests, and needs of teachers in their local contexts.
LES TYPES DE DÉVELOPPEMENT PROFESSIONNEL CONTINU COLLABORATIF EN ÉDUCATION PHYSIQUE: UN DIALOGUE
TIPOS DE DESENVOLVIMENTO PROFISSIONAL COLABORATIVO CONTÍNUO EM EDUCAÇÃO FÍSICA: UM DIÁLOGO
Keywords: Collaboration; Community; Physical Education; Professional Development